Evolution of secondary mitral regurgitation. (9th March 2018) - Bartko, Philipp E; Pavo, Noemi; Pérez-Serradilla, Ana; Arfsten, Henrike; Neuhold, Stephanie; Wurm, Raphael; Lang, Irene M; Strunk, Guido; Dal-Bianco, Jacob P; Levine, Robert A; Hülsmann, Martin; Goliasch, Georg
Abstract: Aims: Secondary mitral regurgitation (MR) drives adverse remodelling towards late heart failure stages. Little is known about the evolution of MR under guideline-directed therapy (GDT) and its relation to cardiac remodelling and outcome. We therefore aimed to assess incidence, impact, and predictors of progressive secondary MR in patients under GDT. Methods and results: We prospectively enrolled 249 patients with chronic heart failure and reduced ejection fraction receiving GDT in this long-term observational study. Of patients with non-severe MR at baseline 81% remained stable whereas 19% had progressive MR. Those patients were more symptomatic ( P < 0.001), had higher neurohumoral activation (encompassing various neurohumoral pathways in heart failure, all P < 0.05), larger left atrial size ( P = 0.004) and more tricuspid regurgitation (TR, P = 0.02). During a median follow-up of 61 months (IQR 50–72), 61 patients died. Progression of MR conveyed an increased risk of mortality—univariately (HR 2.33; 95% CI 1.34–4.08; P = 0.003), that persisted after multivariate adjustment using a bootstrap-selected confounder model (adjusted HR 2.48; 95% CI 1.40–4.39; P = 0.002). In contrast, regression of MR was not associated with a beneficiary effect on outcome (crude HR 0.84; 95% CI 0.30–2.30; P = 0.73). Conclusions: Every fifth patient with chronic heart failure suffers from MR progression. This entity is associated with a more than two-fold increased risk of death even after careful multivariable adjustment. Symptomatic status, left atrial size, TR, and neurohumoral pathways help to identify patients at risk for progressive secondary MR in an early disease process and open the possibility for closer follow-up and timely intervention.